UTILIZATION OF VERMICOMPOST OF ORGANIC WASTE FOR PLANT GROWTH - ANTONY V.SAMROT; VIGNESH MP; VIGNESH V (International Journal of Pharma and Bio Sciences, 2015)
Vermicomposting is the process of decomposing of an organic waste into an organic fertilizer using earthworms. The final product is enriched with nutrients like carbon, nitrogen and essential minerals. In this study work, earthworm - Eudrilus eugeniae (African night crawlers) was utilized to degrade the pretreated bagasse waste and waste papers. Waste paper was found to be degraded in 55-60 days, whereas bagasse took 70 days for degradation. Thus obtained vermicompost was used as fertilizer and tested against the plant (Capsicum annuam) and the growth was observed after 20 days. Vermicompost was found to influence the plant growth.